Mechanistic insights into interactions between ionizable lipid nanodroplets and biomembranes - Čechová, Petra; Paloncýová, Markéta; Šrejber, Martin; Otyepka, Michal (Journal of biomolecular structure & dynamics, 2024)
Delivery of RNA into cells using lipid nanoparticles (LNPs) has been a significant breakthrough in RNA-based medicine, with clinical applicability expanded through the use of ionizable lipids (ILs). These unique lipids can alter their charge state in response to pH changes, which is crucial for pH-triggered endosomal escape and effective lipid-mediated RNA delivery. In this study, we conducted a comprehensive set of molecular dynamics (MD) simulations to investigate interactions between IL-containing lipid nanodroplets (LNDs) and cell membrane models. Using an atomistic resolution model, we investigated the merging process of LNDs with cell membrane models under neutral conditions relevant to an intercellular environment and acidic pH conditions found in late endosomes. Our observations revealed that at neutral pH, LNDs merged with lipid membranes while preserving the bilayer structure. Under acidic conditions, the LNDs remained attached to the bilayer without fusing into the membranes. Importantly, the presence of ILs did not disrupt the original biomembrane structure during the simulation period. The MD simulations provided valuable atomistic insights into the mechanism of interaction between IL-containing nanodroplets and biomembranes, which could aid the rational design of ILs to develop more efficient LNPs for RNA therapies.
Keywords: lipid mixing; Ionizable lipids; membrane simulations; ionizable lipid nanoparticles; molecular dynamics; lipid nanoparticles